The Aesthetics of Stillness and The Quiet Voice in the Literary Style of Kazuo Ishiguro - Usmonova Gavkhar Tolib qizi (Scientific Trends, 2025)
This article explores the aesthetics of stillness and the quiet voice in Kazuo Ishiguro’s literary style, focusing on how emotional restraint, silence, and inner monologue construct profound psychological depth. Ishiguro’s characters often embody passivity, revealing inner conflicts through subdued expression rather than explicit dialogue. The study highlights how this narrative minimalism reflects the author’s vision of memory, guilt, and moral hesitation in postmodern society. Drawing upon narrative theory and stylistic analysis, the paper examines how Ishiguro transforms linguistic silence into a powerful communicative tool. Particular attention is given to The Remains of the Day and Never Let Me Go, where subdued tone and still narration evoke human vulnerability, suppressed desire, and existential reflection that together define the author’s unique poetics of quietness.
Keywords: stillness, silence, introspection, minimalism, narrative voice, emotional restraint, Ishiguro, poetics.